Film rhythm after sound : technology, music, and performance - Jacobs, Lea (University of California Press, 2015)
The seemingly effortless integration of sound, movement, and editing in films of the late 1930s stands in vivid contrast to the awkwardness of the first talkies. Film Rhythm after Sound analyzes this evolution via close examination of important prototypes of early sound filmmaking, as well as contemporary discussions of rhythm, tempo, and pacing. Jacobs looks at the rhythmic dimensions of performance and sound in a diverse set of case studies: the Eisenstein-Prokofiev collaboration Ivan the Terrible, Disney's Silly Symphonies and early Mickey Mouse cartoons, musicals by Lubitsch and Mamoulian,